Aquaporin-4 Autoantibodies From Neuromyelitis Optica Spectrum Disorder Patients Induce Complement-Independent Immunopathologies in Mice - Yick, Leung-Wah; Ma, Oscar Ka-Fai; Ng, Roy Chun-Laam; Kwan, Jason Shing-Cheong; Chan, Koon-Ho (Frontiers in Immunology, 2018)
Neuromyelitis optica spectrum disorders (NMOSD) are central nervous system inflammatory disorders causing significant morbidities and mortality. The majority of NMOSD patients have autoimmunity against aquaporin-4 (AQP4), evidenced by seropositivity for autoantibodies against aquaporin-4 (AQP4-IgG). AQP4-IgG are pathogenic with neuroinflammation initiated upon binding of AQP4-IgG to astrocytic AQP4. Complement activation contributes to astrocytic cytotoxicity, neuroinflammation and tissue necrosis in NMOSD, but the role of complement-independent mechanisms is uncertain. We studied the complement-independent pathogenic effects of AQP4-IgG by passive transfer of IgG from NMOSD patients to mice with breached blood-brain-barrier (BBB). Mice were pretreated with bacterial proteins, and then received daily intraperitoneal injections of IgG purified from AQP4-IgG-seropositive NMOSD patients (IgG(AQP4+)), or IgG from AQP4-IgG-seronegative patients (IgG(AQP4-)) or healthy individuals (IgG(Healthy)) for 8 days. Motor function was tested by walking across narrow beams, and then spinal cords were collected for immunofluorescent analysis. We found that human IgG infiltrated into cord parenchyma of mice with breached BBB without deposition of activated complement products. Cord of mice received IgG(AQP4+) demonstrated loss of AQP4 and glial fibrillary acidic protein (suggestive of astrocyte loss), decrease in excitatory amino acid transporter 2 (EAAT2), microglial/macrophage activation, neutrophil infiltration, patchy demyelination and loss in axonal integrity. Mice received IgG(AQP4+) required longer time with more paw slips to walk across narrow beams indicative of motor slowing and incoordination. Our findings suggest AQP4-IgG induces complement-independent cord pathologies, including astrocytopathy, neuroinflammation, demyelination and axonal injuries/loss, which are associated with subtle motor impairments. These complement-independent pathophysiologies likely contribute to early NMOSD lesion development.